Efficient Helium and Helium Isotopes Separation by Phosphorus Carbide P2C3 Membrane. Issue 2 (23rd November 2021) - Li, Min; Wang, Lu; Lei, Huixia; Yang, Yanmei; Li, Yong‐Qiang; Zhao, Mingwen; Guan, Jing; Li, Weifeng; Qu, Yuanyuan
Abstract: The problem of ever‐increasing industrial demand versus the supply shortage of helium (He) is inevitably encountered by scientists worldwide. Membrane‐based separation technology provides an economical method to alleviate the current He scarcity. In this study, using a combination of first‐principles calculations and molecular dynamics simulations, it is theoretically demonstrated that the phosphorus carbide membrane P2 C3 possesses high efficiency in He separation from the natural gas (H2, N2, CO, H2 O, CO2, and CH4 ) and other noble gas atoms (Ne and Ar). In addition, the He permeance exceeds 10 –4  mol m –2 s –1 Pa –1 over a wide range of temperatures (200–500 K), which is far beyond the industrially acceptable value. Combining the zero‐point‐energy and quantum tunneling effects, the quantum analysis shows that the P2 C3 membrane has great potential for 3 He/ 4 He isotope separation, thus providing a combined means for both He and 3 He isotope separation. The results uncover a new solution of utilizing P2 C3 nanomaterial as a novel medium for gas treatment and the findings of this study will promote experimental efforts in the future. Abstract : Our computations and simulations predict that the phosphorous carbide membrane P2 C3 possesses high efficiency on He purification from natural gas (H2, N2, CO, H2 O, CO2, and CH4 ) as well as other noble gases (Ne and Ar). The quantum analysis indicates that the P2 C3 membrane also has great potential for He isotopes separation.